Financial ratio analysis in stock price: Evidence from Indonesia - Nurul Fitriani; Adib Minanurohman; Gery Lusiano Firmansah (Universitas Pendidikan Indonesia, 2022)
Main Purpose - This study aims to examine the association between financial ratios (including return on assets, debt to equity ratio, cash ratio, and total assets turnover ratio) with stock prices of Indonesian listed company in Indonesia Stock Exchange (IDX) except SIC 6 during 2015 – 2020.Method - This study used Signaling theory and asymmetric information as a theoretical base for testing this association using purposive sampling technique. This research obtained final samples of 1603 firm-year observation and used regression analysis to answer the hypotheses.Main Findings - The results show that return on assets ratio and cash ratio have positive and significant correlation with stock price. While debt to equity ratio has negative and significant correlation with stock price. Meanwhile, total assets turnover ratio has no significant correlation with stock price.Theory and Practical Implications - The results of this study are expected to contribute to both the literature and practice. First, this study expands the literature on the types of financial ratios associated with stock prices as well as the literature on asymmetric information, and second, the results of this study are expected to help investors perform fundamental analysis to estimate the value of the target company.Novelty - This research provides novelty in the form of the latest data updates until 2020 and analysis using old or young company categories which are related to low or high asymmetric information.